Numeracy and Growth Mindset Profiles as a Basis for Differentiated Guidance Service in Islamic Schools - Setyaningrum, Wahyu; Nugroho, Hery; Sofiatun, Isna; Wijaya, Ariyadi (Islamic Guidance and Counseling Journal, 2026)
Up to present, guidance and counseling (GC) services in Islamic schools tend to be homogeneous, often overlooking the diversity of students’ characteristics. This practice overlooks the effectiveness of differentiated guidance. Key factors worth considering for differentiating guidance services are numeracy skills and growth mindset (GM). In this regard, this study aims to: (1) cluster students based on their numeracy skills and GM with K-means techniques; (2) interpret the clusters’ characteristics; and (3) recommend data-driven GC service strategies. Quantitative method K-means clustering was applied to 321 grade VIII students from Islamic junior secondary schools in two provinces in Indonesia. Data from numeracy test and GM questionnaire were analyzed using the Elbow, Silhouette, Kruskal-Wallis, and Dunn post-hoc methods. The result of the study revealed three student clusters: (1) low numeracy and low GM (Double Susceptible); (2) high numeracy and moderate-to-high GM (Empowered); and (3) low numeracy but high GM (Affective Potential). Findings confirm that numeracy skills and GM do not always align, underscoring the need for integrated cognitive and affective interventions. Significant differences in numeracy skills and GM distribution were found between clusters. The different characteristics between clusters lead to diverse service strategies offered for each cluster. These strategies include a cognitive distortion journaling and belief disputes for double susceptible students; career visualization and leadership simulation for empowered students; and mathematical mindfulness and emotion regulation for affective potential students. Data-driven GC services are crucial in supporting students' academic and psychological development.